COMPARATIVE ACTIVITIES OF PHYTOCHEMICAL, ANTIOXIDANT AND ANTIMICROBIAL PROPERTIES OF LEAF EXTRACTS OF Bryophyllum pinnatum (Lam.), Alchornea cordifolia (Schumach. & Thonn.), Acalypha wilkesiana (Muell. Arg) AND SEED EXTRACT OF Citrullus lanatus (Thunb.) - Olude, Oluwagbenga; Akinduti Paul; Akinwande Oluwatobi; Isibor Patrick (Covenant Journal of Physical and Life Sciences, 2022)
The comparative activities of the phytochemical constituents and antioxidant properties of leaf extracts of Bryophyllum pinnattum, Alchornea cordifolia and Acalypha wilkesiana, and seed extract of Citrullus lanatus with their antimicrobial properties were investigated. Qualitative and quantitative phytochemical profile, antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging and ferric reducing antioxidant power (FRAP) of the obtained ethanolic extract were analysed. Using an agar dilution assay, the antimicrobial effects of the ethanolic extracts on the typed Streptococcus faecalis and Pseudomonas aeruginosa were determined. All of the studied extracts contained saponins, tannins, phenols, flavonoids, steroids, terpenoids, reducing sugars, alkaloids and cardiac glycosides; alkaloids was however absent in Citrullus lanatus seed extract. Overall DPPH radical scavenging and FRAP activities of the sample extracts showed a dose-dependent response range of 17.50±0.50 - 89.50±0.50 µg/ml and 0.254±0.002 - 0.434±0.004 µg/ml respectively. Streptococcus faecalis and Pseudomonas aeruginosa showed significant susceptibility to A. wilkesiana and A. cordifolia leaf extract at 400mg/ml compared to less susceptibility at lower concentrations. A. cordifolia leaf extract at MIC 0.16 mg/ml showed highest inhibition to S. faecalis whereas the least inhibition was observed in A. wilkesiana leaf extract against P. aeruginosa at MIC of 2.56 mg/ml. Extracts of A. cordifolia and A. wilkesiana contains phytochemical compounds with significant antioxidant and antimicrobial properties and could be harnessed as natural antioxidant and antibiotics.